Higher education rulemaking : the politics of creating regulatory policy - Natow, Rebecca S. (Johns Hopkins University Press, 2017)
"Many higher education academics and administrators have only vague notions about how the federal government makes regulations governing colleges and universities in the United States, and yet these regulations control many important aspects of the operation of these institutions. What happens after legislation affecting higher education is signed into law? How are specific provisions implemented--especially when the statute's details are unclear? And who determines the details of the programs that a particular law has authorized? In this ... book, higher education policy expert Rebecca S. Natow explores the how and why of the federal regulatory policymaking process as it pertains to higher education, financial aid, and student loan debt. Drawing on in-depth interviews with policy and higher education actors, as well as an extensive review of specific regulations and documents, Natow explains who influences higher education rulemaking and how their beliefs and surrounding contexts guide the policies they enact. She also examines the strategies and powers employed during the process, reveals how technology affects the creation of higher education rules, delves into the multifaceted implications of regulation for students and institutions, and discusses future prospects for higher education rulemaking."--